Influence of Fieldwork on the Preparedness of Food Technology and Bioengineering students for the Job Market: A Case study of EAPI Student Skills Enhancement Program - Kigozi, Julia; Baidhe, Emmanuel; Muzira Mukisa, Ivan; Muyanja, Charles; Namubiru, Leatitiah; Katarikawe, Brenda (Business and Management Research, 2021)
This study aimed at evaluating the influence of fieldwork on the professional and personal skills among Food Technology and Bioengineering (FTB) students of Makerere University. The data was obtained from 40 respondents from three FTB programs (Food Science and Technology, Human Nutrition, and Agricultural Engineering). A semi-structured electronic questionnaire was used to collect the data. The questionnaire comprised of Part 1: Student biography, Part II: Participation in the EAPI student skills enhancement program, Part III: Professional skills, and Part IV: Personal growth. Part I and II consisted of closed-ended questions while Part III and Part IV were evaluated on a 5-point Likert scale (1- Strongly disagree and 5 – Strongly Agree). Descriptive analysis was used to evaluate the student demographic information and participation in the student enhancement program. The reliability of the Likert scale for professional development and personal growth was determined using the Cronbach’s alpha index. The study results indicated that 60% (n=40) of the respondents better understood their career goals through fieldwork, 83% (n=40) increased their skills and knowledge in performing particular tasks, 55% (n=40) changed their attitude and feelings about self and others, while 75% (n=40) had the opportunity to apply theoretical concepts to the actual work environment. Fieldwork stimulated the FTB students’ interest in the field of food processing, mindset change especially concerning job creation, conduct, and prospects. The study findings explain the need to adjust the mode of knowledge delivery and dispensation at the Higher Education Institutions to reduce the rate of unemployment and improve the employability of students.
Keywords: Food technology and bioengineering students; Fieldwork; Skills enhancement; Employability